Из истории крымскотатарского национального движения летом 1919-1920 гг. - Зарубин, В.Г.; Зарубин, А.Г. (Материалы по археологии, истории и этнографии Таврии, 1996)
К концу июня 1919 г. под ударом белых пала Крымская ССР. Воссоздается Таврическая губерния, реальная власть сосредоточивается в руках ее Главноначальствующего генерал-лейтенанта Н.Н.Шиллинга (позднее Главноначальствующий Новороссийской области в составе Одесской, Херсонской и Таврической губерний). Вводится прямая военная диктатура, разворачиваются репрессии, в том числе и против крымскотатарского национального движения, предшествующие этапы которого уже служили авторам темами отдельных исследований (1; 2; 3). Однако его история указанного периода, весьма насыщенная событиями, пока не являлась предметом отдельного изучения, а затрагивалась лишь в общем контексте рассматриваемых проблем When the Crimean Soviet Socialist Republic fell and the military dictatorship of the white was established (the end of June 1919), repression started, against the Crimean Tatars’ National Movement as well. “The Millet’’ (Nation) newspaper was closed, the Crimea Tatars’ Directory was dismissed, its leaders were arrested for their membership in the Communist Party. The power counted on “traditionalists”. They were entrusted to head the re-establishing Religious Mohammedan Government and Vakuf Comission, and “The Millet”, which was allowed to be published again. Milli- firka (National Party) seeks for contacts with Communists. The Tatars did not want to serve in the Army and went into hiding in the woods, reinforcing the detachments of the “Green”. At the underground Regional Committee of RCP(b) they organized Moslem Bureau (Tatar section), defeated by counterintelligence. P.N.Vrangei tried to attract the Tatars. Self-government in cultural-educational and religious fields was promised but not fulfilled. National movement became close with the Communists. The 5th Crimean Tatars regiment was organized as a part of “Red-Green” partizan rebel Army. When the Red Army occupied the Crimea (November, 1920) special government of the Crimean Revolutionary Committee was established, the Crimean Tatars Communists were among its members. They were in the Crimean Regional Committee of RCP(b) with the Moslem section as a part of it. Mill-firka tried to legalize itself but was prohibitted. At the end of 20s - 30s all public figures of the National Movement and many active communists were repressed.